Synthesis and characterization of magnetic-molecularly imprinted polymers for the HPLC-UV analysis of ametryn - Khan, Sabir [UNESP]; Hussain, Sajjad; Wong, Ademar [UNESP]; Foguel, Marcos Vinicius [UNESP]; Moreira Gonçalves, Luís; Pividori Gurgo, Maria Isabel; Taboada Sotomayor, Maria del Pilar [UNESP] (Elsevier, 2018)
Magnetic molecularly imprinted polymer (mag-MIP) were developed for the analysis of ametryn (4-N-ethyl-6-methylsulfanyl-2-N-propan-2-yl-1,3,5-triazine-2,4-diamine), a popular triazine herbicide. Iron oxide (Fe3O4) nanoparticles were synthetized, and then modified with tetraethoxysilane (TEOS) and 3-mercaptopropyltrimethoxysilane (MPS). Then MIPs’ polymerimerization occurred in the nanoparticles’ surface, using ethylene-glycol-dimethacrylate (EGDMA) as the building monomer, 2,2′-azobis(2-methylpropionitrile) (AIBN) as the radical initiator, and 2-vinylpyridine as the functional monomer. The functional monomer was previously chosen by computational simulation. The mag-MIPs’ adsorption behavior well-fitted a Langmuir model (qm of 8.6 mg g− 1, KL of 5.2 L mg− 1) and pseudo first order kinetics (k1 of 2.5 × 10− 4 s− 1). The developed analytical methodology, using high-performance liquid chromatography with UV detection (HPLC-UV), showed suitable selectivity and had a limit of detection (LOD) and quantification (LOQ) of 25 and 82 nmol L− 1, respectively.
Keywords: Analytical chemistry; Environmental analysis; Food analysis; Food quality; Pesticide